Associations of Self-reported Musculoskeletal Pain and Depressive Symptoms among U.S. Healthcare Workers - Oluyomi Oloruntoba; Roaa Aggad; Ashley L. Merianos; Caroline D. Bergeron; Ali Boolani; Kayleigh Gregory; Matthew L. Smith (Health Behavior Research)
Healthcare workers are prone to develop musculoskeletal pain because of the physical demands of their profession. While neck and back pain are believed to have a relationship with depression symptomatology, few studies have assessed this relationship among healthcare workers. The purposes of this study were to identify the: prevalence of musculoskeletal pain and depressive symptoms among healthcare workers; association between musculoskeletal pain and depressive symptoms; and the association between musculoskeletal pain and severity of depressive symptomatology among those with self-reported depressive symptoms. Data from 1,205 healthcare workers in the 2018 National Health Insurance Survey were analyzed. In Phase 1, a logistic regression model was fitted to assess the relationship between self-reported neck and back pain and depressive symptoms. Then, in Phase 2, a logistic regression model was fitted for participants with self-reported depressive symptoms (n=501) to identify associations of neck and back pain with the severity of depressive symptomatology. About 74.9% of the study participants were female, 42.7% aged 41-64 years, 34.5% reported musculoskeletal pain, while 41.7% reported depressive symptoms. Low back pain was the most prevalent body pain (18.7%). Healthcare workers with neck pain only (OR=2.11, P=0.047), low back pain only (OR=2.19, PPHealthcare workers could benefit from multi-faceted public health interventions to simultaneously improve their musculoskeletal pain and depressive symptoms (e.g., ergonomic evaluation, stress management, one-on-one or group counseling).